Development and Prospect of Wind Power Intelligent Operation and Maintenance Technologies in the New Infrastructure Era - WANG Dian; WEN Kun; HU Kaikai; CHEN Yanan; CHEN Gang (Kongzhi Yu Xinxi Jishu)
Confront to the pressure of cost and quality in the parity and bidding era after the rush for installation of wind power, traditional wind farm operation and maintenance management model will become increasingly difficult to meet the high quality development of industry. Combined the current wide application of new infrastructure technologies such as big data, Internet of Things, 5G communication and artificial intelligence, this paper discusses the application prospects of new infrastructure technologies in the field of intelligent operation and maintenance of wind farms. From wind turbine, wind farm and wind-farm groups, using intelligent and digital means, it builds an intelligent wind farm operation and maintenance ecosystem, to achieve cost reduction and efficiency increase in wind farm operation and maintenance management.